Negotiating care and control: Pet euthanasia as phronetic action - Schuurman, Nora (Elsevier Ltd, 2025)
The lives and deaths of animals living with humans have become increasingly medicalised, and the life of a pet usually ends with euthanasia conducted by a veterinarian. In this paper, I explore how pet euthanasia is understood as a good death in interactions between vets and pet guardians in veterinary practice, provided as an act of care for old and seriously ill or injured animals. Drawing from interviews with vets in Finland, I discuss the ways in which care and control are negotiated in the decisions and practices concerning pet euthanasia, and their implications on understandings of old age and death in animals. I approach the task of euthanising an animal without a prospect of continuing life in Aristotelian terms as phronesis, as knowledge about the right and appropriate ways to act in a certain situation.